Litter production in areas of Brazilian "Cerrados" - Peres, José R.R.; Suhet, A.R.; Vargas, Milton A. T.; Drozdowicz, A. (Pesquisa Agropecuaria Brasileira, 2014)
Litter production was measured in Brazilian Cerrado and Cerradão during three successive years. The average yearly production of total litter is 7,800 kg/ha-1 and 2,100 kg/ha-1 in Cerradão and Cerrado, respectively. The leaf-litter (including grasses) represents 76.7% of the total litter in Cerradão and 84% in Cerrado. The rates of litter decomposition determined by direct litter-bag technique are very slow on surface in both ecosystems. The litters from Cerrado and Cerradão have almost the same nutrient storage ability. Samples of litter composed of the parts of predominant plants contain 0.82%-0.85% of N, 0.06% P, 0.16% K, 0.32%-0,34% Ca and 0.12%-0.14%Mg.